Putusan Bebas Atas Dakwaan Tindak Pidana Lingkungan Hidup: Analisis Putusan No. 781/pid/b/2009/PN.CBN. - Hidayatulloh Hidayatulloh (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2016)
Abstract: Acquittal on Accusation of Environmental Crime: Analysis of Verdict Number No. 781/Pid/B/2009/PN.Cbn. The number of industries has increasead rapidly and caused some problems in the environment. With the help of science and technology, most of industries produce toxic waste which is one of the issues of the environmental crime. This paper will analyse the verdict of Cibinong District Court on accusation of environmental crime to Lee Sang Book, the Director of PT. Roselia Texindo. The company working in textile industry was indicted that he has done water pollution in the River Cikuda, Bogor because he has thrown the toxic waste to the river produced by its industry. The verdict is really interesting because the panel of judges have finally decided that Lee Sang Book is not guilty. Based on facts of the trial, he doesn’t break a law to do the environmental crime which was indicted according to the Law Number 23 Year 2007 in Living Environment. Cibinong District Attorney has submitted the unqualified evidence in examination of waste toxic in laboratorium. Furthermore most witnesses and expert witnessed have argued that Lee Sang Book and PT. Roselia Texindo are innocence and have followed the rule. Abstrak: Jumlah industri telah meningkat dengan cepat dan menyebabkan beberapa persoalan lingkungan. Dengan dukungan ilmu pengetahuan dan teknologi, banyak industri menghasilkan limbah berbahaya yang merupakan salah satu isu tindak pidana lingkungan. Tulisan ini menganalisis putusan Pengadilan Negeri Cibinong atas dakwaan tindak pidana lingkungan kepada Lee Sang Book, Direktur PT. Roselia Texindo. Perusahaan yang bergerak di bidang tekstil ini didakwa melakukan pencemaran air sungai Cikuda, Bogor karena membuat limbah kimia hasil proses industri. Pada akhirnya Majelis Hakim memutus bahwa Lee Sang Book tidak bersalah. Berdasarkan fakta-fakta persidangan, ia tidak terbukti melakukan tindak pidana lingkungan yang didakwakan berdasarkan UndangUndang Nomor 23 Tahun 2007 tentang Lingkungan Hidup. DOI: 10.15408/jch.v4i1.2624